Transcriptional and biochemical profiling of defense enzymes in Citrus sinensis during salicylic acid and cinnamon mediated suppression of green and blue mold - Moosa, Anam; Zulfiqar, Faisal; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2022)
Green and blue mold of citrus are threatening diseases that continuously inflict economic post-harvest loss. The suppressive effect of salicylic (SA) and Cinnamomum verum (CV) on green and blue mold of sweet oranges was investigated in this study. Among five tested plant extracts methanolic extract of Cinnamon caused the highest colony growth inhibition of P. digitatum and P. italicum in an in vitro antifungal assay. The methanolic extract of Cinnamon and the application of SA showed the lowest disease incidence and severity of green and blue mold on citrus fruit without affecting the fruit quality. Transcriptional profiling of defense enzymes revealed that the polyphenol oxidase (PPO), phenylalanine ammonia-lyase (PAL), and peroxidase (POD) genes were upregulated in fruit treated with CV, SA, and their combination than the control treatments. The treatment SA+CV caused the highest upsurge in PPO, POD, and PAL gene expression than the control. Furthermore, the biochemical quantification of PPO, POD, and PAL also revealed a similar pattern of results. Our findings unravel the fact that the escalation in the activity of tested defense enzymes is possibly associated with the reduced incidence of blue and green molds. In conclusion, our study unveils the promising suppressive potential of SA+CV against green and blue mold by regulating the expression of PPO, POD, and PAL genes. Therefore, these treatments can find a role as safer alternatives to chemicals in the management of post-harvest green and blue mold.